STUDENTâ€™S PERCEPTION OF THE USE OF SPOTIFY APPLICATION TO IMPROVE LISTENING SKILLS IN GRADE 10 OF SMAN 106 JAKARTA - Galuh Aprilina; Akhmad Haqiqi Maâ€™mun; Zuhad Ahmad (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study aims to analyze students' perceptions of the use of Spotify application in improving English listening skills in class 10 of SMAN 106 Jakarta. This study used a descriptive qualitative method, with data collected through a Likert Scale-based questionnaire and interviews. The questionnaire consisted of statements measuring students' level of agreement on the effectiveness of Spotify, ranging from â€œStrongly Agreeâ€ to â€œStrongly Disagree.â€ The results show that the majority of students have a positive view of Spotify as a learning tool. Features such as lyrics, playlist recommendations, and ease of access were considered helpful in expanding music choices and improving listening skills. In addition, Spotify is also considered effective in improving students' vocabulary acquisition and pronunciation. The results of this study emphasize the importance of technology integration in language learning, with Spotify making a significant contribution in creating a fun and interactive learning atmosphere. Therefore, Spotify can be used as an innovative medium in the English language learning curriculum, especially to improve students' listening skills